Documentation of the Poland farm survey 2000 - Martin Petrick (Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2001)
This documentation summarises the technical information about the Poland farm survey 2000. This survey was recently carried out in co-operation with Polish partners by the Institute of Agricultural Development in Central and Eastern Europe (IAMO) in Halle (Saale), Germany. The topics covered in the documentation are a description and reprint of the questionnaire, sample design, survey organisation and implementation, data management, calculation of certain compound variables, and a brief assessment of the experiences made with the instrument. – – Diese Dokumentation fasst die technischen Informationen über den Poland farm survey 2000 zusammen. Es handelt sich hierbei um eine Befragung von polnischen Landwirten, die vom Institut für Agrarentwicklung in Mittel- und Osteuropa (IAMO) in Halle (Saale) in Zusammenarbeit mit polnischen Partnern durchgeführt wurde. Die in der Dokumentation behandelten Themenbereiche umfassen eine Diskussion und Wiedergabe des verwendeten Fragebogens, Stichprobenziehung, Organisation und Durchführung der Befragung, Datenverarbeitung, Berechnung einiger wichtiger zusammengesetzter Variablen, sowie eine knappe Einschätzung der mit dem Fragebogen im Feld gemachten Erfahrungen.
urn:nbn:de:gbv:3:2-23018
Keywords: C81; 330; Methods of data collection; microeconomic data; survey methodology; Methoden der Datenerhebung; mikroökonomische Daten; Befragung; Landwirtschaft; Befragung; Polen; Statistische Erhebung